Reconstructing Teachers' Communication Styles in Teaching Generation Z: A Digital Pedagogy Perspective - Tsaqilan, Fiqhan Qaulan; Sumarlan, Iman (Fast in Humanities, 2025)
The rapid advancement of digital technology has transformed the educational landscape, particularly in how teachers communicate with students belonging to Generation Z digital natives who demand interactive, personalized, and responsive learning environments. This study aims to examine how teachers reconstruct their communication styles to align with the learning characteristics and expectations of Generation Z students from the perspective of digital pedagogy. Employing a qualitative approach, this research uses classroom observations and in-depth interviews with high school teachers and students to explore the dynamics of teacher-student communication in digitally mediated classrooms. The findings reveal that effective communication with Generation Z requires a shift from traditional, directive styles toward more dialogic, empathetic, and technology-integrated interactions. Teachers who adopt multimodal communication strategies, facilitate two-way engagement, and demonstrate authenticity tend to foster higher levels of student motivation and participation. Additionally, the research highlights the importance of emotional presence and immediacy in maintaining attention and building trust with Generation Z learners. These insights underscore the necessity for educators to continuously adapt their communicative practices in response to evolving digital contexts. The study concludes that reconstructing communication styles is not merely a pedagogical adjustment but a strategic imperative to enhance educational relevance and effectiveness in the 21st-century classroom. The research contributes to the discourse on digital pedagogy by offering practical and theoretical implications for teacher training, classroom interaction design, and the broader transformation of educational communication in the digital age